Gastroenterology manpower: what are the future job prospects for gastroenterology trainees? - Goddard, Andrew F (Frontline Gastroenterol, 2013)
There are over 1100 gastroenterology consultants and approximately 600 higher specialist trainees in the UK in 2012. The speciality has expanded considerably over the past 20 years but will need to expand further over the next 10 years to accommodate those completing training. There is an undoubted need for expansion due to increased demand from an ageing population, cancer screening and an increasing burden of liver disease. However, the UK economy and changes in the way that workforce planning will be made over the next few years will determine whether such expansion occurs. There is accumulating evidence that getting a substantive post in gastroenterology is getting harder and that some trainees are taking up new types of post-training posts. Gastroenterology has historically been a male-dominated speciality but this is changing as more female trainees come through the system. Current trainees have defined expectations about how and where they will want to work as consultants and these expectations are different according to their gender. Trainees are also aware that the way of consultant working is likely to change considerably in the next decade with increased need for acute medicine in hospitals and 7-day working. Medical workforce planning has always been very difficult. There are major changes planned in how training will be controlled in the NHS over the next few years, both locally and nationally. The future for gastroenterology is unclear but almost certainly trainees will have to be more flexible in how and where they work.